The effect of conjugated linoleic acid on lipid metabolism in the hamster and the sheep - Flux, Claire Louise (2005)
The term conjugated linoleic acid (CLA) refers to a range of geometric and positional isomers of linoleic acid. Recent research suggests a variety of potential health benefits with consumption of dietary CLA. These include a reduction in body fat deposition that has been demonstrated in a number of monogastric species including the mouse, rat, hamster and pig. This thesis describes the effects of CLA on lipid metabolism in sheep, where CLA may be useful in reducing carcass fat and improving fatty acid profile. The results are contrasted with those in the hamster, a model monogastric species, previously shown to respond to CLA. Ovine adipose tissue metabolism was studied in explants maintained in culture and incubated with a mixture of CLA isomers and individual isomers. Total lipogenesis, and the formation of saturated and monounsaturated fatty acids were examined. Results show no effect of CLA (mixed or individual isomers) on total lipogenesis or desaturation of fatty acids. Furthermore, there was no effect on mRNA concentration for acetyl coenzyme A carboxylase (ACC) or stearoyl coenzyme A desaturase (SCD). The effect of feeding CLA (protected from rumen degradation) to sheep, on lipogenic gene expression was then investigated. While there was no evidence of a decrease in total fat deposition, there was a decrease in the proportion of monounsaturated fatty acids in the tissues. As there was no effect on SCD mRNA levels, it appears likely that CLA inhibits SCD activity rather than affecting gene expression. A further feeding study was undertaken in Golden Syrian hamsters. As in the sheep, CLA feeding reduced the monounsaturated fatty acid content of the tissues but did not change the SCD mRNA concentration in adipose tissue or liver. This further supports the suggestion that CLA directly inhibits SCD activity. Unlike the sheep, there was an overall decrease, of approximately 10%, in total carcass fat. However, paradoxically, there was an increase in adipose tissue ACC and fatty acid synthase (FAS) mRNA concentrations. Thus, suppression of lipogenic enzyme expression does not appear to be the mechanism by which CLA reduces fat deposition.